Nitrogen Use Efficiency, Allocation, and Remobilization in Apple Trees: Uptake Is Optimized With Pre-harvest N Supply - Tan, Bi Zheng; Close, Dugald C.; Quin, Peter R.; Swarts, Nigel D. (Frontiers in Plant Science, 2021)
Optimizing the utilization of applied nitrogen (N) in fruit trees requires that N supply is temporally matched to tree demand. We investigated how the timing of N application affected uptake, allocation and remobilization within 14-year-old ‘Gala’/M26 apple trees (Malus domestica Borkh) over two seasons. In the 2017-18 season, 30 g N tree-1 of 5.5 atom % 15N-calcium nitrate was applied by weekly fertigation in four equal doses, commencing either four weeks after full bloom (WAFB) (pre-harvest) or one week post-harvest, or fortnightly, divided between pre- and post-harvest (50:50 split). Nitrogen uptake derived from fertilizer (NDF) was monitored by leaf sampling before whole trees were destructively harvested at dormancy of the first season to quantify N uptake and allocation, and at fruit harvest of the second season to quantify the remobilization of NDF. The uptake efficiency of applied N fertilizer (NUpE) was significantly higher from pre-harvest (32.0%) than from the other treatments (~17%). Leaf NDF concentration, an indicator of N uptake, increased concomitantly only when pre-harvest N was applied. Pre-harvest treated trees allocated more than half of the NDF into fruit and leaves and stored the same amount of NDF into perennial organs as the post-harvest treatment. Subsequent spring remobilization of NDF was not affected by the timing of N fertigation from the previous season. A seasonal effect of remobilization was observed with a decrease in root N status and a reciprocal increase in branch N status at fruit harvest of season two. These findings represent a shift in the understanding of dynamics of nitrogen use in mature deciduous trees and indicate that current fertilizer strategies need to be adjusted from post-harvest to primarily pre-harvest N application, to optimize N use efficiency. This approach can provide adequate storage N to support early spring growth the following season with no detriment to fruit quality.